IMF contingency financing for middle-income countries with access to private capital markets : an assessment of the proposal to create a Reserve Augmentation Line - Kregel, Jan (UN New YorkUS, 2007)
Reviews the conditions that led to the loss of IMF control over balance of payments financing, and how private capital flows increased the liquidity requirements for system stability. Examines how the IMF responded to these problems, before assessing whether the Reserve Augmentation Line represents a sufficient improvement to the contingent Credit Line, in providing signals that will reduce the probability of crisis for countries implementing it, as well as conditions to convince countries to actually use it.